1991
DOI: 10.1113/jphysiol.1991.sp018583
|View full text |Cite
|
Sign up to set email alerts
|

In mice, the muscle weakness due to age is absent during stretching.

Abstract: SUMMARY1. The contractile force was compared in isolated soleus muscles from young (2-5-8 months old) and aged (28-31 months old) mice. Force was measured at 25 'C during isometric tetanic contractions during isovelocity stretching and shortening contractions.2. The normalized isometric force was lower by 13-3 % in muscles from aged mice. Muscles from young and aged mice produced 0-951 +0-031 N mg-1 (n = 12) and 0-824+0-048 N mg-' (n = 9) respectively. The relaxation time, from 90 to 10% of the tetanic force, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
58
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 12 publications
10
58
1
Order By: Relevance
“…For instance, Phillips et al measured specific force, defined as isometric tension (T 0 ) normalized to muscle cross sectional area (CSA), in isolated soleus muscles of young and old mice during eccentric and concentric muscle contractions. The results of this study confirm that agerelated deficits in specific force during stretching of the muscle are minimal (Phillips et al, 1991). In other words, muscle weakness due to age is manifested only in concentric contractions, while tension during stretching is preserved in old muscles.…”
Section: Cellular Mechanismssupporting
confidence: 80%
See 1 more Smart Citation
“…For instance, Phillips et al measured specific force, defined as isometric tension (T 0 ) normalized to muscle cross sectional area (CSA), in isolated soleus muscles of young and old mice during eccentric and concentric muscle contractions. The results of this study confirm that agerelated deficits in specific force during stretching of the muscle are minimal (Phillips et al, 1991). In other words, muscle weakness due to age is manifested only in concentric contractions, while tension during stretching is preserved in old muscles.…”
Section: Cellular Mechanismssupporting
confidence: 80%
“…It has been suggested that the stretch produced during eccentric contractions might shift myosin heads into a strongly bound state (Lombardi and Piazzesi, 1990). This, in turn, would reduce during eccentric contractions the age-related force deficits commonly observed during either isometric or concentric contractions (Phillips et al, 1991). It is still unclear though, why this stretch-induced phenomenon does not bring about additional tension in young muscle fibers (Fig.…”
Section: Cellular Mechanismsmentioning
confidence: 97%
“…As mentioned above, a large R int,down requires a large force to be exerted during the following negative work phase (stretching), whereas a large R int,up requires a large force to be exerted during the preceding positive work phase (shortening). The finding that R int,down is less affected by age than R int,up suggests that the deficit in force during stretching is less than the deficit in force during shortening, which, as mentioned above, is a characteristics of aged muscle [80][81][82][83][84][85].…”
Section: The Landing-takeoff Asymmetry In Old Humansmentioning
confidence: 74%
“…In old age, muscular force is reduced, but the deficit in force is less during stretching than during shortening. This has been shown in experiments on isolated muscle specimens [80,81] and in vivo on humans [82][83][84][85]. The effect of this change of muscle contractile properties with age on the mechanics of locomotion is unknown.…”
Section: The Landing-takeoff Asymmetry In Old Humansmentioning
confidence: 96%
“…The latter includes fiber loss and atrophy (Larsson et al 1979;Sato et al 1984;Lexell et al 1988), impairments in the excitation-contraction process (Delbono et al 1995;Wang et al 2002), and perturbations to actomyosin cross-bridge function (Larsson et al 1997; Thompson and Brown 1999;Lowe et al 2001;Frontera et al 2000;Hook et al 2001;Krivickas et al 2001). These factors are specific to the mode of muscle contraction, impacting force during isometric and shortening contractions but having much less effect on force during lengthening or eccentric, muscular activity (Porter et al 1997;Poulin et al 1992;Phillips et al 1991;Ochala et al 2006;Hortobagyi et al 1995).…”
Section: Introductionmentioning
confidence: 99%